2017
DOI: 10.1007/s13224-017-0965-8
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of Strings After Postplacental Intracesarean Insertion of CuT380A and Cu375 Intrauterine Contraceptive Device: A Randomized Comparative Study

Abstract: Both Cu375 and CuT380A IUD are safe postpartum method of contraception but Cu375 if used for intracesarean IUD insertion increases the incidence of visible IUD strings. Hence, it avoids radiological investigations and invasive procedures at follow-up visits required to locate the IUD when strings are not visible. CTRI/2015/09/006221.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…After postplacental insertion at the time of cesarean delivery, IUD strings may be more likely to be visualized for LNG-IUDs than for CuT380A IUDs [31], likely because of the LNG-IUD's longer strings. In addition, strings may descend into the vagina with further involution of the postpartum uterus and thus may become visible over time after postplacental insertion [74,76,77]. One prospective cohort study of 348 women who received a CuT380A IUD after vaginal or cesarean delivery found an increase in IUD string visibility over time, with 90% and 32% of strings visible at 6 weeks after vaginal and cesarean deliveries, respectively, compared with 98% and 72% at 12 months [74].…”
Section: Missing Stringsmentioning
confidence: 99%
“…After postplacental insertion at the time of cesarean delivery, IUD strings may be more likely to be visualized for LNG-IUDs than for CuT380A IUDs [31], likely because of the LNG-IUD's longer strings. In addition, strings may descend into the vagina with further involution of the postpartum uterus and thus may become visible over time after postplacental insertion [74,76,77]. One prospective cohort study of 348 women who received a CuT380A IUD after vaginal or cesarean delivery found an increase in IUD string visibility over time, with 90% and 32% of strings visible at 6 weeks after vaginal and cesarean deliveries, respectively, compared with 98% and 72% at 12 months [74].…”
Section: Missing Stringsmentioning
confidence: 99%
“…Also, the removal of IUCD with visible strings is easy. 7 In this study, authors observed that patients were more apprehensive of the strings visible at introitus but not about non-visibility.…”
Section: Discussionmentioning
confidence: 60%
“…Visibility of strings at 6-weeks follow up visit was 62% for CuT380A and 92% for Multiload Cu375 in a study by Kavita et al 7 Lower expulsion rate of 3.33% at 6 weeks follow up was observed in this study as shown in chart 3 due to our technique of insertion, similar to 4.49 % in a study by Swathi et al and 4% in CuT380A and 2% in multiload Cu375 in a study by Kavita et al 7,11 Previous studies indicate that expulsion rates after intra-caesarean IUCD insertion are much lower probably due to correct placement at the fundus. 7 Spontaneous expulsion rate is 0.84% in intra-caesarean insertion compared to vaginal insertion (1.84%) in a study by Gupta P et al 13 Counseling of the women and confirmation of IUCD in uterine cavity by ultrasound are important to reassure and encourage women to continue PPIUCD. 5 In all cases irrespective of strings visibility, ultrasound was required to confirm intrauterine position and relation to the fundus because contraceptive efficacy is better when it is in normal position and less than 1cm away from the fundal endometrium.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations